2016
DOI: 10.1016/j.jcis.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular exchange on water droplet size analysis as determined by diffusion NMR: The W/O/W double emulsion case

Abstract: Using the water diffusion data, the use of a low measurement temperature and diffusion delay Δ could reduce the droplet size overestimation resulting from extra-droplet water diffusion, but this undesirable effect was inevitable. Detailed analysis of the diffusion data revealed that the extra-droplet diffusion effect was due to an exchange between the inner water phase and the oil phase, rather than by exchange between the internal and external aqueous phase. A promising data analysis procedure for retrieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…[9][10][11] This method measures signal attenuation arising from free and restricted self-diffusion of molecules, and this last one is dependent on the size of cavities. [5][6][7][12][13][14][15] However, a mathematical model is needed to predict the DSD from the measured signal attenuation. Several modeling approaches were suggested to relate the measured signal attenuation to the selfdiffusion coefficient within spherical cavities, including: Short Gradient Pulse (SGP), [16] which assumes that no motion of the spins occurs during the time that the field gradient pulses are applied, Gaussian Phase Distribution (GPD), [17] which assumes Gaussian distributed phases under the field gradient, and Block Gradient Pulse (BGP) approximation which is based on the solution of the Bloch-Torrey equation under steady gradient.…”
Section: Pulsed-field Gradient Nuclear Magnetic Resonance (Pfg-nmr)mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] This method measures signal attenuation arising from free and restricted self-diffusion of molecules, and this last one is dependent on the size of cavities. [5][6][7][12][13][14][15] However, a mathematical model is needed to predict the DSD from the measured signal attenuation. Several modeling approaches were suggested to relate the measured signal attenuation to the selfdiffusion coefficient within spherical cavities, including: Short Gradient Pulse (SGP), [16] which assumes that no motion of the spins occurs during the time that the field gradient pulses are applied, Gaussian Phase Distribution (GPD), [17] which assumes Gaussian distributed phases under the field gradient, and Block Gradient Pulse (BGP) approximation which is based on the solution of the Bloch-Torrey equation under steady gradient.…”
Section: Pulsed-field Gradient Nuclear Magnetic Resonance (Pfg-nmr)mentioning
confidence: 99%
“…This observation can be related to the higher Laplace pressure of smaller droplets. Vermeir et al [14,23] found that exchange occurs from the inner water phase to the oil phase while diffusion to the external water phase was negligible during the NMR measurement.…”
Section: Pulsed-field Gradient Nuclear Magnetic Resonance (Pfg-nmr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple emulsions were also measured. Quantification and interpretation of data are highly demanding for this type of emulsions …”
Section: Lf‐nmr In Oil Production Formulation and Usementioning
confidence: 99%
“…Taking into account that oil molecules significantly experience restricted diffusion due to a fat crystal network with a minimal solid fat content (SFC) of 50%, it seems reasonable to assume that water and solute molecules will experience comparable SFC‐dependent restrictions on diffusion when travelling through the fat phase. In case of bulk crystallization in the oil phase of an osmotically balanced W/O/W double emulsion, an increasing SFC has been noted to reduce the release rate of encapsulated marker compounds and to reduce the water exchange kinetics between the water compartments . Herzi and Essafi recently demonstrated that the release of magnesium ions was dependent on the SFC provided that the oil phase of the W/O/W globule consisted of a continuous crystal network.…”
Section: Introductionmentioning
confidence: 99%